Health literacy of children and adolescents - Machová, Alena; Brabcová, Iva (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2018)
Health literacy[2TD$DIF] is a person's ability to search for relevant sources regarding health, understand the information, and use it adequately to improve their behaviour in order to support their own health. The goal of this article is to analyze academic publications which are focused on the assessment of the health literacy of children and adolescents. We used the method of content analysis. The sources were searched for in the databases EBSCO, ProQuest, ScienceDirect, Scopus, Web of Science and Willey between April and May 2018. Based on the analysis of the sources, it is possible to say that most of the studies were carried out outside of Europe. Aside from one qualitative and one quantitative-qualitative study, all studies were quantitative. They mostly use the standardized assessment scales TOFHLA, REALM-Teens and NVS. The respondents were children and adolescents. Some studies were focused on children and adolescents with specific needs or social problems.
Zdravotní gramotnost dětí a adolescentů
Keywords: Health; literacy; children; adolescents; Zdravotní gramotnost; děti; adolescenti